The Potent of Constituents from Leunca Fruits (Solanum nigrum Linn.) as Anti-Skin Aging against TYRP-1: Molecular Docking and ADME-Tox - Kelutur, Faruk Jayanto; Hadi, Agriyaningsih Oktaviana (Proceeding International Conference on Religion, Science and Education, 2024)
Leunca fruits are a source of natural antioxidants with compounds that have been reported, namely quercetin, solasodine, solanine, solamargine, and solasonine. However, its effectiveness as an anti-skin aging has not been studied. In the skin, melanin is produced by melanocytes in the deepest layer of the epidermis, thus protecting the skin from damage caused by sunlight radiation. Moreover, pregnant women can also cutaneous changes due to hyperpigmentation by skin lesions. If the formation of abnormal melanin, it is necessary to inhibit the tyrosinase enzyme, TYRP-1. This research was conducted by predicting the interaction between compounds of leunca fruits and the enzyme of TYRP-1 using Audock Tooks 1.5.6. Then, from the molecular docking results, ADMET-Tox was carried out with pre-ADMET to determine transdermal drug delivery and safety when used as a product. The results of in silico molecular docking showed that solasodine and quercetin had a higher binding affinity (G, -8.58 and -7.74 kcal/mol; Ki, 517.15 and 2110 nM) compared to kojic acid (-5.50 kcal/mol; 92720 nM) as a reference. The amino acid His192 becomes a crucial residue when hydrogen interacts based on visualization. While ADME-Tox, solasodine fulfills the safety of the transdermal route. Therefore, this compound can potentially be anti-skin aging from the leunca fruits. Apart from that as a drug topical for pregnant women when melanogenesis in the epidermal melanocytes.